Analisis Ekonomi Terapan Berkelanjutan Budidaya Porang sebagai Tanaman Sela di Bawah Tegakan Hutan Pinus Jatirejo - Soesanto Soesanto; Mega Darmi Novita (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This research aims to examine the cultivation system of porang as an intercrop in pine forests, analyze production costs, revenue, and income, as well as assess the feasibility of porang farming in Jatirejo District, Mojokerto Regency. The research employed a census method with 20 purposively selected porang farmers as respondents. Data were analyzed by calculating production costs, revenue, income, and the Revenue Cost Ratio (R/C). The results showed that most farmers applied the row planting system, which achieved higher productivity (4,507 kg/ha) compared to the random planting system (4,029 kg/ha), as orderly arrangement supports optimal growth. The average production cost in the row planting system was IDR 9,697,833, with revenue of IDR 42,250,000 and income of IDR 32,552,167. Meanwhile, the random planting system incurred an average production cost of IDR 8,369,500, with revenue of IDR 26,437,500 and income of IDR 18,068,000. The R/C ratio of the row planting system was higher, at 4.3, compared to 3.1 in the random planting system. These findings indicate that the row planting system is more profitable and cost-efficient, and porang farming is economically feasible to be developed as an intercrop in pine forests.